Fazlur Rahman's Thoughts On Islamic Education And Its Relevance In The Contemporary Era - Siti Waspiatul Kamilah; Nikhlah Ziyadaturrohmah; Tazkia Nur Fateha; Andi Rosa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Islamic education has an important position in shaping human beings who have faith, knowledge, morals, and are able to think critically and creatively. However, in practice, the Islamic education system is still faced with various problems, such as the separation between religious and general sciences and the weak integration between Islamic values and the development of modern science. In this context, Fazlur Rahman's thinking offers a significant update. As a modern Muslim intellectual, he initiated the concept of Islamic education based on the values of the Qur'an and emphasized the importance of the development of reason and rational intellect. Through the double movement method, Fazlur Rahman proposes a contextual interpretation approach to the Qur'an, namely by understanding the meaning of revelation based on the historical background of its descent, then implementing its values in modern life. His ideas focus on the unification of religious and general sciences, the renewal of learning methods, and the formation of critical, innovative, and moral character of students. This study uses a qualitative-descriptive approach with the type of literature research, through analysis of Fazlur Rahman's works and relevant literature. The results of the study show that Fazlur Rahman's educational thinking has high relevance to today's Islamic education system, especially in answering the challenges of globalization and modernization. The integration between Qur'anic values, scientific rationality, and the spirit of reform developed by Fazlur Rahman can be the foundation for the formation of an Islamic education system that is relevant, progressive, and contextual with the times.